1990
DOI: 10.1093/geront/30.3.308
|View full text |Cite
|
Sign up to set email alerts
|

Helping Medicare Beneficiaries Choose Health Insurance: The Illness Episode Approach

Abstract: Lacking objective, comprehensible information about health care coverage options, Medicare beneficiaries rarely understand the consequences of alternative purchasing decisions. We describe the Illness Episode Approach, a method providing information on Medicare itself, Medigap policies, and HMOs. The method presents calculations of seniors' out-of-pocket costs under different insurance options for 13 common illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Sofaer et al (76,78) conducted a quasi-experimental evaluation of an innovative approach to provide people with Medicare information about the financial consequences of their health care coverage decisions. All participants were enrolled in a three-hour workshop covering the same topics but using different materials.…”
Section: How Stable Are Patient Definitions and Ratings Of Quality?mentioning
confidence: 99%
See 1 more Smart Citation
“…Sofaer et al (76,78) conducted a quasi-experimental evaluation of an innovative approach to provide people with Medicare information about the financial consequences of their health care coverage decisions. All participants were enrolled in a three-hour workshop covering the same topics but using different materials.…”
Section: How Stable Are Patient Definitions and Ratings Of Quality?mentioning
confidence: 99%
“…When all dimensions of care are combined, the national overall score is 72. Nationwide, hospitals are doing best on physical comfort (82), involving family and friends (76), and coordination of care [see also (76)]. They are doing worst on emotional support (65), transition to home (69), and providing information and education [see also (69)].…”
Section: Hospitalsmentioning
confidence: 99%
“…Actual health service use for a given health problem clearly varies somewhat by insurance plan (e.g., Manning et al 1987); however, it is unclear how to incorporate such behavioral responses into the cost presentation strategies appropriately. Sofaer and her colleagues implemented the illness episode material using the same assumption, justifying the utilization patterns they illustrated as clinically appropriate (Sofaer and Kenney 1989;Sofaer et al 1990). …”
Section: Decision-support Strategiesmentioning
confidence: 98%
“…Sturman, Boudreau, and Corcoran (1996) speculate on the potential consequences of giving consumers decision-support information about out-of-pocket costs. We identified two published approaches for presenting such information to consumers: the ''total cost'' strategy (Francis 1996) and the ''illness episode'' strategy (Sofaer and Kenney 1989;Sofaer et al 1990). Both strategies aim to provide participants with a basis for comparing the expected annual outof-pocket costs of different plans.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Among the indicators, patient care ratings (i.e., survey data) were best understood while "undesirable event" records-based data (e.g., rates of pediatric asthma hospitalization) were least understood, followed by "desirable event" records-based data (e.g., pediatric immunization rates) McGee, Sofaer, and Kreling 1996). Earlier studies by Sofaer and her colleagues (Sofaer et al 1990;Sofaer, Kenney, and Davidson 1992) showed that comparative information on something as concrete and interpretable as the costs of illness episodes by plan type had little impact on Medicare beneficiaries' understanding of Medicare in general or on their own health plan type.…”
Section: Comparative Plan Informationmentioning
confidence: 99%